Concepções apresentadas por estudantes do ensino médio da Baia de Camamu e de São Miguel das Matas com relação ao fenômeno das marés - De Jesus, Antonio Marcos (2018)
The phenomenon of the tides has aroused the curiosity of mankind for thousands of years, and with this has emerged over time several explanations for such phenomenon. This work goes into this perspective of talking about the tides, based on the conceptions presented by two groups of students studying in different regions, one group residing in the Bay of Camamu and experiencing this phenomenon almost daily and the second group is in a coast region called Vale do Jiquiriça in the municipality of São Miguel das Matas city. All students answered a questionnaire with personal questions and about computer science, gravitation and tidal phenomena. The issues were analyzed and discussed. Subsequently interventions were made using a website, developed during the research entitled "Universo na escola" (educational product), with activities related to the themes present in the initial questionnaire, allowing students to interact with the object of study